Glomus tumer management outcomes of the hand (مجلة البحوث الأكاديمية, 2025)
Background: Glomus tumors are rare, benign, and painful vascular tumors arising from the glomus body, most found in the subungual region of the fingers. Despite their typical clinical presentation, diagnosis is often delayed for years.Methods: A retrospective case series was conducted on 7 patients treated at Misurata Medical Centre between June 2020 and October 2023. Clinical presentation, imaging, surgical technique, and postoperative outcomes were analyzed. Pain relief was measured using the Visual Analog Scale (VAS), and patients were followed up for 6 months to assess recurrence and nail deformity.Results: All patients (100%) reported pain and localized tenderness; 66% had cold sensitivity. The average delay in diagnosis was 73 months. Surgical excision using the transungual approach led to complete symptom relief in all patients. VAS scores improved from 9.3 preoperatively to 0.59 at 6 weeks. Nail regrowth was complete in all cases; minor deformities occurred in 2 patients. No recurrence was observed during follow-up.Conclusion: Glomus tumors of the fingers can be effectively diagnosed clinically and treated with surgical excision. Early recognition and precise surgical technique result in excellent functional and cosmetic outcomes with minimal recurrence.